2019
DOI: 10.3390/cells8080828
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Serves as Substrate of 3-Mercaptopyruvate Sulfurtransferase and Stimulates Sulfide Metabolism in Colon Cancer Cells

Abstract: Hydrogen sulfide (H2S) is an endogenously produced signaling molecule. The enzymes 3-mercaptopyruvate sulfurtransferase (MST), partly localized in mitochondria, and the inner mitochondrial membrane-associated sulfide:quinone oxidoreductase (SQR), besides being respectively involved in the synthesis and catabolism of H2S, generate sulfane sulfur species such as persulfides and polysulfides, currently recognized as mediating some of the H2S biological effects. Reprogramming of H2S metabolism was reported to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 88 publications
2
25
1
Order By: Relevance
“…Our data indicate that NAC is unlikely to be a significant co-substrate for the MPST reaction in cells. In contrast, a prior study, reported a 1.3-fold higher catalytic efficiency with NAC versus cysteine (23). Since the MPST activity was reported in arbitrary fluorescence units in this study (23), a direct comparison with our data is not possible.…”
Section: Kinetic Comparison Of Mpst1 and Mpst2 Isoforms With Cysteinecontrasting
confidence: 75%
See 1 more Smart Citation
“…Our data indicate that NAC is unlikely to be a significant co-substrate for the MPST reaction in cells. In contrast, a prior study, reported a 1.3-fold higher catalytic efficiency with NAC versus cysteine (23). Since the MPST activity was reported in arbitrary fluorescence units in this study (23), a direct comparison with our data is not possible.…”
Section: Kinetic Comparison Of Mpst1 and Mpst2 Isoforms With Cysteinecontrasting
confidence: 75%
“…In some protozoans, MPST is fused to thioredoxin (21,22), suggesting that it might be the physiologically relevant sulfane sulfur acceptor in higher organisms as well. N-acetyl cysteine (NAC), widely used as a cysteine precursor, was recently reported as an alternative acceptor of MPST, exhibiting a 1.3-fold higher catalytic efficiency than cysteine (23). Furthermore, the antioxidant activity of NAC was attributed to MPST-dependent synthesis of H2S followed by its oxidation to sulfane sulfur species via the mitochondrial sulfide oxidation pathway (24), inducing an oxidative shift in mitochondria but not in the cytoplasm.…”
Section: -Mercaptopyruvate Sulfur Transferase (Mpst) Catalyzesmentioning
confidence: 99%
“…High MPST activity and expression have been proven in numerous cancer cell lines and tissues, including human prostate tissue, urothelial carcinoma cells of bladder, colon cancer and human glioblastoma-astrocytoma and neuroblastoma cell lines [15,[40][41][42]. As shown in our paper, the MCF-7 line is characterized by relatively high MPST levels.…”
Section: Discussionsupporting
confidence: 52%
“…Cysteine degradation catalyzed by CAT and MST ( Figure 1B ) is not deeply explored in cancer, since MST is more enzymatically efficient at a pH higher than the physiological, thus the role of CBS and CSE is considered more relevant in cancer biology ( 92 ). However, Zuhra et al ( 93 ) demonstrated recently, in a colon cancer cell line, that MST can produce H 2 S from N-acetylcysteine instead of cysteine-derived 3-mercaptopyruvate. Nonetheless, MST is constitutively expressed in normal differentiated cells and some studies have detected its expression or activity in various cancer cell lines and primary tumors, including brain, colon, liver, kidney, lung and bladder cancer, and melanoma [reviewed in ( 35 )].…”
Section: Cysteine As a Carbon Source In Cancermentioning
confidence: 99%